ChemInform Abstract: An Approach Toward the Syntheses of Triazolo Benzoxazines, Triazolo Quinoxalines, Triazolo Benzodiazepines, Triazolo Benzoxazepines, and Triazolo Benzothiazines via a Simple and Convenient Protocol Using Basic Alumina as Solid Support. Issue 37 (16th September 2014) - Chatterjee, Nivedita; Sarkar, Swarbhanu; Pal, Rammyani; Sen, Asish Kumar
Abstract The solid support plays a dual role as it eliminates the use of an organic solvent as well as a Pd‐catalyst.